2019
DOI: 10.1002/sim.8336
|View full text |Cite
|
Sign up to set email alerts
|

Mediation analysis of time‐to‐event endpoints accounting for repeatedly measured mediators subject to time‐varying confounding

Abstract: In this article, we will present statistical methods to assess to what extent the effect of a randomised treatment (versus control) on a time‐to‐event endpoint might be explained by the effect of treatment on a mediator of interest, a variable that is measured longitudinally at planned visits throughout the trial. In particular, we will show how to identify and infer the path‐specific effect of treatment on the event time via the repeatedly measured mediator levels. The considered proposal addresses complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…The exact nature of the relationship between any baseline characteristic, including BMI, and CV benefit of liraglutide and semaglutide (via glycaemic control and/or weight loss and/or other mechanisms) remains difficult to establish, 3,8 with published meta-analysis results showing that baseline BMI was not associated with achieved glycaemic control across seven different antihyperglycaemic treatments. 9 Thus, the doseresponse curves for any treatment may differ for MACE, glucose levels and weight, and our analyses have shown that there appeared to be generally no effect of baseline BMI on MACE.…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of the relationship between any baseline characteristic, including BMI, and CV benefit of liraglutide and semaglutide (via glycaemic control and/or weight loss and/or other mechanisms) remains difficult to establish, 3,8 with published meta-analysis results showing that baseline BMI was not associated with achieved glycaemic control across seven different antihyperglycaemic treatments. 9 Thus, the doseresponse curves for any treatment may differ for MACE, glucose levels and weight, and our analyses have shown that there appeared to be generally no effect of baseline BMI on MACE.…”
Section: Discussionmentioning
confidence: 99%
“…In these models, we used the change from baseline as a time-dependent covariate and included the baseline value also as described by Vansteelandt and colleagues. 12 The mediated proportion was calculated as the difference in log hazard ratios (HRs) between the models without and with the mediator, divided by the log HR from the model without the mediator. STATA 14.2 (StataCorp LP, College Station, TX, USA) was used for all analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Vansteelandt method may also adjust for postbaseline confounders, such as concomitant medication, by including them as covariates in the models. Further details of this method have been published separately (10).…”
Section: Vansteelandt Methodsmentioning
confidence: 99%
“…In the present exploratory analyses, we sought to identify potential mediators for the CV benefit observed with liraglutide using data from the LEADER trial. We explored these with several mediation methods, including a new statistical methodology designed to integrate sequential confounders (a limitation of existing methods for mediation analysis) (10).…”
mentioning
confidence: 99%